Carbon Materials as Adsorbents and Catalysts - Oladipo, Akeem Adeyemi; Ogulewe, Ezinne Favour; Ansari, Hoda; Aleshinloye, Abimbola Ololade; Gazi, Mustafa (CRC Press, 2024)
One of the most pressing environmental issues is the prevalence of pharmaceutical residues and their byproducts in various environmental media. These compounds are notorious for their ubiquity, harmful accumulation, and resistance to breakdown. Antibiotics and synthetic hormones are among the most commonly detected pharmaceuticals in the environment, and their presence has been linked to the emergence of antimicrobial-resistant genes and various health concerns for both humans and aquatic life. Unfortunately, the typical techniques utilized in wastewater treatment facilities do not adequately remove pharmaceutical remnants and their byproducts. Of the tertiary treatment alternatives, adsorption and catalysis have proven to be the most effective and are commonly employed. Carbon-based materials, including those derived from biochar, activated carbon, carbon-derived quantum dots, graphene, carbon nanotubes, and hierarchical porous carbon, are showing promise as eco-friendly adsorbents and catalysts due to their remarkable physical and chemical properties, pore architectures, and abundant sources of raw materials. This chapter presents a comprehensive overview of the properties and applications of common carbonaceous materials for the purpose of eliminating pharmaceutical residues and their metabolites through adsorption and catalysis. In addition, the underlying mechanisms of adsorption and catalytic degradation, as well as the key factors that influence these processes, are critically discussed. The aim of this research is to encourage further investigation into the design of carbon-based adsorbents and catalysts, with a specific focus on the effective removal of emerging pollutants. © 2025 selection and editorial matter, P.V. Nidheesh and Aydin Hassani; individual chapters, the contributors.